New Insights Into Subsurface Stratigraphy Northwest of Ascraeus Mons, Mars, Using the SHARAD and MARSIS Radar Sounders. Issue 6 (10th June 2022) - Shoemaker, E. S.; Carter, L. M.; Garry, W. B.; Morgan, G. A.; Plaut, J. J.
Abstract: The Tharsis Montes volcanoes on Mars are the source of laterally extensive lava flows and other volcanic deposits generating a complex stratigraphy throughout the Tharsis Volcanic Province. We use SHAllow RADar (SHARAD) and Mars Advanced Radar for Subsurface and Ionospheric Sounding (MARSIS) observations in a region northwest of Ascraeus Mons to determine the composition, density, thickness, and spatial distribution of these emplaced volcanic materials. We identified subsurface reflectors along 43 SHARAD and five MARSIS observations. Reflectors in the volcanic plains are interpreted to be sequences of basaltic lava flows with interspersed pyroclastic material, dust, or regolith during a hiatus in activity. Others correspond to the base of three major flow fields. Several plain reflectors were detected by both MARSIS and SHARAD. Other notable reflectors were identified near Ascraeus' flank where lava buried glacially derived sediment. We derived thickness and other material properties for flows using their distinct topographic boundary visible in the radar images. Permittivity ranged from 7.0 to 11.2 corresponding to lava flow densities of 3.20–3.52 g/cm 3 . Flow thicknesses ranged from 19.8 to 60.2 m. Loss tangents were low for the flow fields ranging from 0.024 to 0.043. Loss tangents in the plains ranged from 0.010 to 0.076. Higher loss tangents correspond to lossier regions that may have higher concentrations of radar absorbing minerals like hematite. Surface roughness controls where reflectors are detected. SHARAD detects the base of three out of the four flow fields in this region with muted surface roughness from dust mantling and erosion. Plain Language Summary: The Tharsis Volcanic Province is host to the largest volcanoes on Mars and has been a center of Martian volcanism for much of the planet's history. Sequences of volcanic deposits such as lava flows or ash give a glimpse into the evolution of Mars' surface and its shallow subsurface. We used observations from the orbiting SHAllow RADar and Mars Advanced Radar for Subsurface and Ionospheric Sounding radar sounders that probe beneath these deposits. Radar detects subsurface stratigraphy where there is an interface between materials with differing densities. Using radar, we mapped the shallow subsurface extents and thicknesses of volcanic and glacial deposits in the region northwest of the Ascraeus Mons volcano. We measured thicknesses of three out of four lava flow fields where the radar detected their base contacting the surrounding volcanic plains. These interfaces were generated via volcanic ash, dust, or eroded material deposited on the surfaces of the older, buried lava flows of the plains. Other interfaces resulted from the burial of glacial sediment by later lava flows near the base of Ascraeus Mons. This study extends knowledge of the surface volcanic and glacial processes that have shaped the Tharsis Volcanic Province into the shallow subsurface. Key Points: The SHAllow RADar (SHARAD) and Mars Advanced Radar for Subsurface and Ionospheric Sounding radar sounders detect numerous clusters of subsurface interfaces along 48 observations northwest of Ascraeus Mons Some subsurface interfaces may arise from glacial sediment buried by ponded lava near the western flank of Ascraeus Mons Surface roughness controls where SHARAD detects subsurface interfaces at the bases of three out of four large lava flow fields